Dermatologic manifestations of thyroid disease: a literature review - Cohen, Benjamin; Cadesky, Adam; Jaggi, Shuchie (Frontiers in Endocrinology, 2023)
Purpose of Review Introduction: Thyroid hormone is considered one of the key regulatory hormones for skin homeostasis. Multiple organs are affected by the release of peripheral thyroid hormones (T4 and T3) further regulating various functions at a cellular level. Specifically, skin is considered an important target organ in which the thyroid hormone has a significant impact. Multiple skin diseases are associated with thyroid hormone dysregulation. However, other striking dermatologic manifestations are seen in nails and hair as well. Hypothyroidism, hyperthyroidism, and thyroid cancer can have an array of cutaneous manifestations, and we present the recent updates in this field. Methods: A PubMed search was performed for updates in any new skin disease findings and treatments between 2010 and 2022. Research published in the past decade and previously known foundational skin findings associated with thyroid disease were presented in this review. Conclusion: Cutaneous manifestations of thyroid disease is one of the first notable signs of thyroid hormone dysregulation. This article reviews the recent updates on the thyroid and skin interplay, and it further discusses overt visible findings and various available treatment modalities.